Intracranial Atherosclerotic Disease - Maria Khan; Imama Naqvi; Asha Bansari; Ayeesha Kamran Kamal (Stroke Research and Treatment)
Intracranial atherosclerotic disease (ICAD) is the most common proximate mechanism of ischemic stroke worldwide. Approximately half of those affected are Asians. For diagnosis of ICAD, intra-arterial angiography is the gold standard to identify extent of stenosis. However, noninvasive techniques including transcranial ultrasound and MRA are now emerging as reliable modalities to exclude moderate to severe (50%–99%) stenosis. Little is known about measures for primary prevention of the disease. In terms of secondary prevention of stroke due to intracranial atherosclerotic stenosis, aspirin continues to be the preferred antiplatelet agent although clopidogrel along with aspirin has shown promise in the acute phase. Among Asians, cilostazol has shown a favorable effect on symptomatic stenosis and is of benefit in terms of fewer bleeds. Moreover, aggressive risk factor management alone and in combination with dual antiplatelets been shown to be most effective in this group of patients. Interventional trials on intracranial atherosclerotic stenosis have so far only been carried out among Caucasians and have not yielded consistent results. Since the Asian population is known to be preferentially effected, focused trials need to be performed to establish treatment modalities that are most effective in this population.